2007
DOI: 10.1144/290.10
|View full text |Cite
|
Sign up to set email alerts
|

Strain partitioning of active transpression within the Lebanese restraining bend of the Dead Sea Fault (Lebanon and SW Syria)

Abstract: Recent neotectonic, palaeoseismic and GPS results along the central Dead Sea fault system elucidate the spatial distribution of crustal deformation within a large (c.180-km-long) restraining bend along this major continental transform. Within the ‘Lebanese’ restraining bend, the Dead Sea fault system splays into several key branches, and we suggest herein that active deformation is partitioned between NNE–SSW strike-slip faults and WNW–ESE crustal shortening. When plate motion is resolved into strike-slip para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
69
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(79 citation statements)
references
References 58 publications
(120 reference statements)
6
69
0
Order By: Relevance
“…1, represents the most important structure because it connects the southern and the northern parts of the DSFS. This fault has a strikeslip displacement of 4-6 mm year -1 , while the Roum Fault shows a strike-slip rate of 1 mm year -1 Daeron et al 2004;Nemer and Meghraoui 2006;Gomez et al 2007). A recent study by Gomez et al (2007) showed that the Yammouneh Fault accommodates most of the expected strike-slip motion, which indicates that this fault is accumulating strain.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…1, represents the most important structure because it connects the southern and the northern parts of the DSFS. This fault has a strikeslip displacement of 4-6 mm year -1 , while the Roum Fault shows a strike-slip rate of 1 mm year -1 Daeron et al 2004;Nemer and Meghraoui 2006;Gomez et al 2007). A recent study by Gomez et al (2007) showed that the Yammouneh Fault accommodates most of the expected strike-slip motion, which indicates that this fault is accumulating strain.…”
Section: Introductionmentioning
confidence: 93%
“…This fault has a strikeslip displacement of 4-6 mm year -1 , while the Roum Fault shows a strike-slip rate of 1 mm year -1 Daeron et al 2004;Nemer and Meghraoui 2006;Gomez et al 2007). A recent study by Gomez et al (2007) showed that the Yammouneh Fault accommodates most of the expected strike-slip motion, which indicates that this fault is accumulating strain. These authors deduce that the fault's present day lack of seismicity is likely a reflection of the slow rate of strain accumulation in a locked fault system.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations